Review on Listeriosis in small ruminants and public health significance in Ethiopia - Belete Gobasho Kundul; Mohammedkemal Mustefa Ame (International Journal of Veterinary Science and Research - Peertechz Publications, 2022)
Listeria monocytogenes is a bacterium mostly transmitted to man through food and it can cause mild gastroenteritis or severe infections of the bloodstream and/or the central nervous system, or abortion, depending on host susceptibility. Listeriosis is a serious illness caused by eating food contaminated with the bacterium Listeria, which is a Gram-positive psychotropic, facultatively anaerobic, none sporulating, motile, small rod. It displays characteristic tumbling motility that is facilitated by the presence of peritrichous flagella. Motility is temperature-dependent, showing high motility at 20-30°C when the flagellar expression is maximum. L. monocytogenes is ubiquitous in the environment and can be found in soil, water, feces, silage, effluent foods, and sewage. It has the ability to form biofilms which can contribute to its ability to colonize food processing facilities. The primary mode of transmission for Listeria is through soil contamination and ingestion of contaminated feed. Calves that develop the septicemic disease may acquire infection from contamination of the cow teat from the ingestion of milk containing the organism or from a cow with subclinical bacteremia, through the navel from the environment and also as congenital infection. Infection with Listeria. monocytogenes usually follow ingestion of contaminated feed and may result in septicemia, encephalitis, and abortion. There are few clinical features that are unique to listeriosis. Therefore, clinicians must consider a variety of potential causes of infection, including viral infections (influenza) and other bacterial infections that may cause sepsis or meningitis. Cook thoroughly raw food from animal sources, such as beef, pork, or poultry. Wash raw vegetables thoroughly before eating. Keep uncooked meats separate from vegetables and from cooked foods and ready-to-eat foods. Avoid raw (unpasteurized) milk or foods made from raw milk. Wash hands, knives, and cutting board and can contact with before and after handling cooked foods.